Studies of the Soviet Institute of Forests - Tulunin, B. (Indian Forester, 1959)
An account of the Institute of Forests of the USSR Academy of Sciences is presented. Details regarding its various branches are furnished and the forest researches pursued are briefly touched upon. These researches have enabled the USSR to extend its green frontiers into the arid and semi-arid lands. The concept of Biogeocenosis, which regards a forest type as a well-balanced complex of soil, vegetation, environment and animal life is discussed. An analytical study based on such a complex is a useful tool in the hands of the foresters to enable them to manipulate the forest operations in the most beneficial manner.